CHARACTERIZATION OF A HYDRAULIC SYSTEM WITH MULTIPLE EXHAUSTS (Global Journal of Advanced Engineering Technologies and Sciences, 2017)
Hydraulic systems are traditionally constituted by one suction and one exhaust connected by pipes. Between the suction and the exhaust, pumps and many devices can be placed (reduction, expansion, valves, equipment, etc.). Hydraulic projects usually consist in predicting the fluid volumetric flow rate (volumetric capacity) that can flow through the hydraulic system according to its main features: piping size (diameter and length), kind of accessories, pump power, inlet and outlet pressure conditions, and the elevation of the suction and exhaust. However, this study investigated the behavior of a hydraulic system with the addition of multiple exhaust lines just after the pump, connected to a distributor. In this case, predicting the volumetric capacity of a hydraulic system was more complex, because the new fluid flow rate must be distributed according to the characteristics of each exhaust. Mathematically, a set of nonlinear equations was established based on the fundamentals of Fluid Mechanics and it was solved simultaneously. This methodology predicted the volumetric capacity according to the number of attached piping lines and other features of the hydraulic system, such as length, diameter, roughness, elevation, and pump power. Experimental validations demonstrated that the deviations of the numerical method adopted in this study were lower than 4%. The addition of multiple exhausts was beneficial because it considerably increased the volumetric capacity for the same pump power installed. As an example, when the number of exhausts changed from 2 to 4, from 4 to 6, and from 6 to 8, the volumetric capacity of the experimental system increased in 86%, 45%, and 24%, respectively. This study also indicated the variables that most affected the volumetric capacity: the piping diameter, the elevation of the exhausts, and the amount of exhausts, in this order.